Review and Prospects of Key Technologies for Integrated Systems in Hydrogen Production from Offshore Superconducting Wind Power - Liufei Shen; Cheng Zhang; Feiyue Shan; Long Chen; Shuai Liu; Zhiqiang Zheng; Litong Zhu; Jinduo Wang; Xingzheng Wu; Yujia Zhai (Energies)
Hydrogen production from renewable energy sources is a crucial pathway to achieving the carbon peak target and realizing the vision of carbon neutrality. The hydrogen production from offshore superconducting wind power (HPOSWP) integrated systems, as an innovative technology in the renewable energy hydrogen production field, holds significant market potential and promising development prospects. This integrated technology, based on research into high-temperature superconducting generator (HTSG) characteristics and electrolytic water hydrogen production (EWHP) technology, converts offshore wind energy (OWE) into hydrogen energy locally through electrolysis, with hydrogen storage being shipped and controlled liquid hydrogen (LH2) circulation ensuring a stable low-temperature environment for the HTSGs’ refrigeration system. However, due to the significant instability and intermittency of offshore wind power (OWP), this HPOSWP system can greatly affect the dynamic adaptability of the EWHP system, resulting in impure hydrogen production and compromising the safety of the LH2 cooling system, and reduce the fitness of the integrated system for wind electricity–hydrogen heat multi-field coupling. This paper provides a comprehensive overview of the fundamental structure and characteristics of this integrated technology and further identifies the key challenges in its application, including the dynamic adaptability of electrolytic water hydrogen production technology, as well as the need for large-capacity, long-duration storage solutions. Additionally, this paper explores the future technological direction of this integrated system, highlighting the need to overcome the limitations of electrical energy adaptation within the system, improve product purity, and achieve large-scale applications.